Echo Intensity Reliability From Two Ultrasound Systems. (September 2020) - Rabello, Rodrigo; Pompeo, Klauber D.; de Almeida Paz, Isabel; Lanferdini, Fabio J.; Pinto, Ronei S.; Vaz, Marco A.
Objective: Echo intensity measurements are highly influenced by ultrasound system and parameters used for measurement, making comparisons of results obtained from different ultrasound machines difficult. Therefore, it is necessary to understand how reliability changes when using different ultrasound systems and parameters. Materials and Methods: ALOKA SSD4000 and GE LOGIQ P6 systems were used to compare rectus femoris echo intensity in 16 healthy young subjects (eight women) using different depths (D), gains (G), and frequencies (F). The following settings were adopted: ALOKA1 (D6/G30/F7.5), ALOKA2 (D6/G45/F7.5), ALOKA3 (D6/G30/F10), LOGIQ1 (D6/G50/F15), LOGIQ2 (D6/G0/F15), LOGIQ3 (D6/G0/F10), and LOGIQ4 (D6/G30/F10). Intraclass correlation coefficient, standard error of the measure, minimum difference, and Bland-Altman tests were performed to calculate reliability and agreement between systems' settings. Results: ALOKA1 × LOGIQ1, ALOKA1 × LOGIQ4, and ALOKA3 × LOGIQ1 showed moderate to high ICCs and agreement on the Bland-Altman test. Conclusion: Echo intensity varies between systems and parameters, but reliability can be increased by adjusting the ultrasound settings.